TECHNOLOGY AND EDUCATION - * (TADQIQOTLAR.UZ, 2024)
The new century is an era of active development of science and technology. Modern society lives at a rapid pace of change, witnessing successive technological breakthroughs affecting our daily lives. Compared to the primitive era, the way people live in modern times is significantly different, and these changes can be partly attributed to progress in science and technology. The impact of science and technology is felt in various spheres of human life, including the field of education. This article describes the essence of using innovative pedagogical technologies in education and its role and importance in improving the quality of education. Also, this article discusses the effectiveness of using innovative pedagogical technologies in the educational process and offers suggestions for a new approach to the educational process in higher education institutions.